ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HASIL PEMERIKSAAN STUDI DI INSPEKTORAT KABUPATEN WONOSOBO - Sulastiningsih Sulastiningsih; Agus Susilo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
The purpose of this research is to determine the influence factors of supervisor work experience, supervisor independency, supervisor objectivity, integrity and competencies supervisor on the quality of the inspection results in Wonosobo regency Inspectorate. Population of this research was overall of Supervisor Officers, Auditors Functional Officers (PFA), P2UPD functional and technical staff who has been certified auditor functional. Population number of this research is 31 people, and all in the sample. Data collection method using by questionnaires. To test the quality of data used validity and reliability testing. Test results declared valid and reliable. After the classical assumption, namely normality test, multicollinearity and heteroskedasticity test revealed that linear multiple regression model enabled for predict the effect of work experience, independency, objectivity, integrity and competencies of inspectors against to quality of the audit results. Regression equation is : Y = -3.235 + 0.074X1+ 0.210X2+ 0.259X3+ 0.205X4+ 0.338X5. The results by testing the overall model obtained F value of 203.465 with a significance probability is 0.000. F value of 203.465 is greater than the F table (2.60), and the significance value 0.000 is less than the probability value of 0.05. Thus, work experience, independency, objectivity, integrity and competencies, has significantly affect simultaneously against the quality of test results. The results t-test obtained t-test value is greater than t-table for five independent variables, so the partial variable: work experience, independency, objectivity, integrity and competencies has significantly influences against the quality of inspection results.